(untitled) (Research, Society and Development, 2020)
This experiment aimed to evaluate the effect of weight gain, body condition score and antral follicle count on the fertility of cows subjected to fixed-time artificial insemination. To this study, it was used 194 Nelore, pluriparous cows, between the 30th and the 45th day of the postpartum period. The cows were weighed, was classified by the body condition score and a transrectal ultrasound was performed in the ovaries to identify the corpus luteum and for counting the antral follicles. Then, the females were submitted to a hormonal protocol to perform the artificial insemination in fixed time. Thirty days after the artificial insemination, the cows were weighed again and the pregnancy was diagnosed by transrectal ultrasound. The pregnancy rate did not interact (P>0.05) with the body score condition, nor the presence of the corpus luteum, neither with the antral follicles count. The weight gain between the artificial insemination moment and the pregnancy diagnosis showed an interaction (P = 0.02) with the pregnancy rate. The weight gain average between the FTAI and the pregnancy diagnosis was 9.0 kg. The animals that gained up to 73 kg, showed higher pregnancy rate. In conclusion, the weight gain between the artificial insemination in fixed time and the pregnancy diagnosis influenced the pregnancy rate.